Unsuspected leptospirosis is a cause of acute febrile illness in Nicaragua. - Megan E Reller; Elsio A Wunder; Jeremy J Miles; Judith E Flom; Orlando Mayorga; Christopher W Woods; Albert I Ko; J Stephen Dumler; Armando J Matute (Public Library of Science (PLoS), 2014)
Epidemic severe leptospirosis was recognized in Nicaragua in 1995, but unrecognized epidemic and endemic disease remains unstudied.To determine the burden of and risk factors associated with symptomatic leptospirosis in Nicaragua, we prospectively studied patients presenting with fever at a large teaching hospital. Epidemiologic and clinical features were systematically recorded, and paired sera tested by IgM-ELISA to identify patients with probable and possible acute leptospirosis. Microscopic Agglutination Test and PCR were used to confirm acute leptospirosis. Among 704 patients with paired sera tested by MAT, 44 had acute leptospirosis. Patients with acute leptospirosis were more likely to present during rainy months and to report rural residence and fresh water exposure. The sensitivity of clinical impression and acute-phase IgM detected by ELISA were poor.Leptospirosis is a common (6.3%) but unrecognized cause of acute febrile illness in Nicaragua. Rapid point-of-care tests to support early diagnosis and treatment as well as tests to support population-based studies to delineate the epidemiology, incidence, and clinical spectrum of leptospirosis, both ideally pathogen-based, are needed.